If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(x-3)+9x=2x+5
We move all terms to the left:
-3(x-3)+9x-(2x+5)=0
We add all the numbers together, and all the variables
9x-3(x-3)-(2x+5)=0
We multiply parentheses
9x-3x-(2x+5)+9=0
We get rid of parentheses
9x-3x-2x-5+9=0
We add all the numbers together, and all the variables
4x+4=0
We move all terms containing x to the left, all other terms to the right
4x=-4
x=-4/4
x=-1
| 5r−8=9r−12 | | 3+12y-1=8y+30-3y | | u-5/6=21/4 | | 8x+4-6x=-10x+28 | | 43+2x=65 | | 3+12y-1=8y+30-2 | | 4(x+1)=2x4 | | x.4x-5=2x+7 | | 6xx=1.5 | | 3(2x+8)=80 | | 3(3y+1)=20 | | +12y-1=8y+30-3y | | g(2)=4,000(6)0.3(2) | | 2/3(6x─15)=4x-2 | | -2(4n+7)+6n+4=-2 | | Y2-8y+15=0 | | 3+12y-1=8y+30-2y | | 2.00x=1.50 | | -3(x-3)+9x=2x=5 | | 2(3y-8)=30 | | X^2-30x+85=0 | | 15=-0.2x+20 | | -6y=14=32-4y | | 19x+8=89 | | -8y=-36-15 | | 12−1/3y=3y+5−2y−1 | | 2x+8=11x-1 | | 11u=9u+6 | | –10p=–7−9p | | 232=54-w | | 1.50x=2.00 | | 5(4x-6)-9x=18 |